Peningkatan Aktifitas dan Hasil Belajar Siswa pada Mata Pelajaran Kesehatan, Keselamatan Kerja (K3) dan Higiene Sanitasi dengan Menggunakan Media Power Point - Yunizar Yunizar (EduInovasi: Journal of Basic Educational Studies, 2022)
The background of this study was low activity and student learning outcomes in subjects Health, Safety (K3) and Sanitation Hygiene at SMK Negeri 2 Depok. The purpose of research is to improve the activity and student learning outcomes in subjects K3 and Sanitation Hygiene using media power point. This type of research is classroom action research conducted with three cycles. The study consists of four stages, namely planning, action, observation, and reflection. The low yield obtained learners learn the mastery of learning materials due to various factors. Low learning outcomes are influenced by two factors, namely internal and external factors ". Internal factors include the state of students' physical and spiritual conditions, external factors include the state of the environment and factor approaches, methods and media used by teachers in learning activities. K3 learning process and Sanitation Hygiene in SMK N 2 Depok, teachers deliver material to the media assisted lecture method whiteboard and markers. This resulted in less attracted the attention of students when the teacher delivering the material, often seen students turn to ask permission out of the classroom, and some students are more often talked with friends rather than pay attention to the subject matter. To overcome this can be helped by using varying media in order to enhance the students' attention on learning. The use of instructional media can arouse desire and new interests, encourage motivation and stimulation of learning activities ".The data used are primary data obtained directly from students in the form of activities and student learning outcomes. The data obtained were tabulated and calculated the percentage of events and achievement of learning objectives. The results showed media power point can increase the activity and student learning outcomes in subjects K3 and Sanitation Hygiene. It can be seen from the increase in activity and learning outcomes of students achieving mastery learning is above the target. Keywords: health and safety, Sanitation Hygiene, student learning outcomes,